Your Diamond Dreams Cut Open My Arteries Poems by Else Lasker-Schüler - Lasker-Schüler, Else (UNC Studies in the Germanic Languages and Literatures, 1982)
Critics have called Else Lasker-Schüler the greatest of all German women poets and one of the finest Jewish poets. This large and representative selection of translations by Robert P. Newton, supplemented by a biographical and critical introduction and a selected bibliography, was the first substantial presentation of her works in English at its original publication in 1982.